Different Types of Intraoperative Hypotension and their Association with Post-Anesthesia Care Unit Recovery - Lerzan Dogan; Serap Aktas Yildirim; Tugce Sarikaya; Halim Ulugol; Bulent Gucyetmez; Fevzi Toraman (Ubiquity Press, 2023)
Background: The underlying causative mechanism leading to intraoperative hypotension (IOH) may vary depending on the stage of anesthesia and surgery, resulting in different types of IOH. Consequently, the incidence, severity, and postoperative complications associated with IOH types may differ. This study explores the association between IOH types and post-anesthesia care unit (PACU) recovery, with a focus on duration and complications. Methods: From May 2022 to December 2022, we included 4776 consecutive surgical patients aged ≥18 who underwent elective surgery with planned overnight stays at Acibadem Altunizade Hospital and received general anesthesia. Post-induction hypotension (pIOH) was defined as a decrease in blood pressure during the first 20 minutes after anesthesia induction, while maintenance intraoperative hypotension (mIOH) referred to a decrease in blood pressure occurring after the 20th minute following induction, with or without preceding pIOH.Results: Among the included patients, 22.13% experienced IOH, with a higher prevalence observed among females. Patients with mIOH exhibited higher rates of bleeding, transfusions, hypothermia, longer stays in the PACU, and increased oxygen requirements. The duration of anesthesia did not increase the likelihood of IOH. Multivariate logistic regression analysis revealed that ephedrine usage, hypothermia, the need for additional analgesics, nausea, and vomiting were factors associated with longer PACU duration. Older patients (≥65), patients with ASA≥2 status, those undergoing major surgery, experiencing unexpected bleeding, and exhibiting hypothermia at the end of anesthesia had a higher likelihood of requiring vasopressor support. Conclusions: Patients experiencing hypotension, particularly during the maintenance of anesthesia, are more prone to complications in the PACU and require closer monitoring and treatment. Although less common, mIOH has a more significant impact on outcomes compared to other factors affecting PACU recovery. The impact of mIOH on PACU duration should not be overlooked in favor of other factors. Registration: Clinicaltrials.gov identifier: NCT05671783.